Penggunaan Media Teka Teki Silang Dalam Meningkatkan Kemampuan Berpikir Kritis Pada Mata Pelajaran Fikih - Lintang Kusumawardhani Susanto Putri; Eka Naelia Rahmah (Prodi Pendidikan Keagamaan Islam, 2024)
This research is motivated by the fact many students still experience difficulties in understanding the material due to inappropriate use of learning media. The purpose of this research is to determine the use of crossword puzzle media in improving students' critical thinking skills in Fiqh subjects at MI Mumtaza Pondok Cabe. This research using qualitative descriptive research. Primary data sources for this research are school principals, PAI teachers, and class 5 students at MI Mumtaza Pondok Cabe. Data collection techniques use observation, interviews and documentation. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The results of this research show that the using of crossword puzzles in learning works well and effectively improves students' critical thinking skills. This is supported by the application aspect of the media, namely suitability to the objectives, the crossword puzzle media helps students achieve. Appropriateness: This media is suitable for use in jurisprudence subjects. In terms of students' condition, students can solve crossword puzzles well. The research results show that the use of crossword puzzles is effective in improving students' critical thinking skills. This media is appropriate to the learning objectives, appropriate for fiqh lessons, and students can complete it well. The infrastructure at the school is adequate, and there are no additional costs for its construction. The teacher provides clear explanations of the steps before students work, and students understand the material better after using this media. Crossword media can also hone critical thinking skills through interpretation, analysis, evaluation, inference, explanation and self-regulation.